Le Paysage de la vallée de l’Ondaine. Complexité et paradoxe de la transformation et de la narration d’un territoire post minier - Georges-Henry Laffont; Luc Rojas (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Once a center of mining and industrial activity throughout several centuries, the Ondaine Valley, between Saint-Etienne and Firminy, remains today marked by traces of the industrialization that shaped the territory, especially in regards to its coal mining history. Despite a period of mourning beginning in the late 1970s, local actors still have difficulties taking mining heritage into account within their territorial reconversion policies. Primarily composed of three cities with populations fluctuating between 8,000 and 16,000 inhabitants, the Ondaine Valley gives us a view of a territory in which three different "projects" are expressed in terms of mining heritage management. The landscape is thus the expression of these "projects", considering the mining heritage as an element that contributes to the construction of an imaginary, which is also a resource to be exploited and sometimes a story to be forgotten in favor of another narrative of the territory.